Anxiety Appraisal in Mothers of Preterm Neonates Admitted in Critical Care Unit - Gul, Rafia; Fatima, Samer; Khurshid, Samina; Niamat, Sidra; Anwar, Zahid; Ahdi, Saher Gul (Archives of Clinical and Biomedical Research, 2025)
Background: Mothers of premature neonates often confront various psychological challenges including postpartum depression, anxiety, and elevated stress levels. However, anxiety has not received the necessary emphasis in routine clinical practice and research, often going unnoticed. There is insufficient data regarding the utilization of specific tools for screening maternal anxiety in hospitalized preterm infants. The study aimed to determine the prevalence of maternal anxiety and its risk factors among mothers of premature neonates admitted to the intensive care unit. Methods: Following Institutional Review Board (IRB) approval, a descriptive cross-sectional study was conducted at level-III Neonatal Unit, Fatima Memorial Hospital Shadman, Lahore over the duration of 25 months, (July 2021-July 2023). Mothers were screened for anxiety using the Perinatal Anxiety Screening Scale (PASS) having 31 items. Comparative descriptive statistics and multiple logistic regression were applied to identify all risk factors while taking p <0.05 as significant. Results: Out of 430 mothers, 28.1% experienced anxiety. Statistically significant factors for maternal anxiety include young age, urban residence, higher education, smoking, diabetes, depression/anxiety diagnosis, primiparity, delivery complications, maternal involvement in neonatal care, breastfeeding, fear of handling preterm infants at home, and prematurity-related concerns, as well as gestational age, birth weight, and weight for gestational age (p < 0.05). Among all these, however, prematurity <28 weeks (p < 0.001, AOR 496, 95% CI 22.5–10951) and 28-31+6 weeks (p < 0.001, AOR 265, 95% CI 14–5010), along with primiparity (p = 0.001, AOR 16.483, 95% CI 3.287–82.648), and SGA (p = 0.025, AOR 8.9, 95% CI 1.3–60.6) increase while extended family system protects from maternal anxiety (p = 0.002, AOR 0.25, 95% CI 0.106–0.595). Conclusion: Every third mother in our study population who delivered prematurely experienced anxiety. The younger gestational age, first-time motherhood, and small for gestation age (SGA) neonate increase while the extended family system serves as a protective factor against maternal anxiety.